Genetic and Biochemical Analysis of the Yeast Plasma Membrane Ssy1p-Ptr3p-Ssy5p Sensor of Extracellular Amino Acids - Forsberg, Hanna (American Society for Microbiology, 2001)
Ssy1p and Ptr3p are known components of a yeast plasma membrane system that functions to sense the presence of amino acids in the extracellular environment. In response to amino acids, this sensing system initiates metabolic signals that ultimately regulate the functional expression of several amino acid-metabolizing enzymes and transport proteins, including multiple, genetically distinct amino acid permeases. We have found that SSY5 encodes a third component of this amino acid sensing system. Mutations in SSY5 manifest phenotypes that are indistinguishable from those resulting from either single ssy1 and ptr3 mutations or ssy5 ssy1 and ssy5 ptr3 double mutations. Although Ssy5p is predicted to be a soluble protein, it exhibits properties indicating that it is a peripherally associated plasma membrane protein. Each of the three sensor components, Ssy1p, Ptr3p, and Ssy5p, adopts conformations and modifications that are dependent upon the availability of amino acids and on the presence of the other two components. These results suggest that these components function as part of a sensor complex localized to the plasma membrane. Consistent with a sensor complex, the overexpression of SSY1 or the unique N-terminal extension of this amino acid permease homologue inactivates the amino acid sensor in a dominant-negative manner. Each of the components of the Ssy1p-Ptr3p-Ssy5p (SPS) signaling system undergoes rapid physical changes, reflected in altered electrophoretic mobility, when leucine is added to cells grown in media lacking amino acids. Furthermore, the levels of each SPS sensor component present in whole-cell extracts diminish upon leucine addition. The rapid physical alterations and reduced levels of sensor components are consistent with their being downregulated in response to amino acid availability. These results reveal the dynamic nature of the amino acid-initiated signals transduced by the SPS sensor.